2014
DOI: 10.26618/ejpbi.v3i1.798
|View full text |Cite
|
Sign up to set email alerts
|

Lecturer’s Strategies in English Speaking Class

Abstract: This research aimed to reveal (1) Speaking as one of subject skills in which English-major students must pass at. It is presented into three or four semesters; speaking 1 up to speaking 3 or 4 starts from the first semester in some universities. Each level has description -in speaking 1 the students are taught basic speaking skills, starting from greetings, introducing oneself and others, etc., to make them capable of using simple English in daily conversation; speaking 2 various functions/topics are introdu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…The perception of some teaching strategies that investigated this present study was in line with other studies conducted by Mojares (2013) and Daddi & Haq (2014) at the university level. In Mojares' study, he found that the lecturers most often used the lecture method and brainstorming.…”
Section: The Effect Of Students' Perception On Teaching Strategy Tsupporting
confidence: 92%
See 2 more Smart Citations
“…The perception of some teaching strategies that investigated this present study was in line with other studies conducted by Mojares (2013) and Daddi & Haq (2014) at the university level. In Mojares' study, he found that the lecturers most often used the lecture method and brainstorming.…”
Section: The Effect Of Students' Perception On Teaching Strategy Tsupporting
confidence: 92%
“…It indicated that those strategies were appropriate for teaching English. While Haq & Daddi (2014) proposed an audio-based presentation, topic-based presentation, peer share idea, role play, discussion, and simulation as a strategy in teaching English.…”
Section: The Effect Of Students' Perception On Teaching Strategy Tmentioning
confidence: 99%
See 1 more Smart Citation